Hazard identification in fabrication industry using Hazard Identification and Risk Assessment (HIRA) and Job Safety Analysis (JSA) - Lely Herlina; Nustin Merdiana Dewantari; Atia Sonda; Moch. Rizky Mulyana (Universitas Sultan Ageng Tirtayasa, 2022)
Mild steel roofing is increasingly being used in simple construction processes. Prima Land Company dominates the lightweight steel roof market share in Pandeglang. However, accidents can come in its manufacturing process, and the potential hazards have yet to be fully measured. Therefore, this study aims to identify, assess, and provide risk control to prevent and reduce work accidents at Prima Land Company. The methods used are Hazard Identification and Risk Assessment (HIRA) and Job Safety Analysis (JSA). HIRA is used to identify the hazard in the mild steel roofing process area, whereas JSA is used to identify hazards in forklifts and lift operations. The results showed that eight activities have potential risks in manufacturing lightweight steel roofs and 16 risks in operating forklift machines and finished loading goods into vehicles. In the HIRA method, the risk category assessment is uniform. However, the highest risk of 38% is extreme risk for sand sprinkling activities, untied and closed plug cables or switches, and transfer of coil raw materials.